Differential cytotoxic activity of pharmacological inhibitors of IGF1R-related pathways in JAK2V617F driven cells. (September 2022) - Fernandes, Jaqueline Cristina; Fenerich, Bruna Alves; Alves-Silva, Antônio Bruno; Fonseca, Natasha Peixoto; Coelho-Silva, Juan Luiz; Scheucher, Priscila Santos; Rego, Eduardo Magalhães; Figueiredo-Pontes, Lorena Lôbo; Machado-Neto, João Agostinho; Traina, Fabiola
Abstract: Myeloproliferative neoplasms (MPN) belong to a group of clonal diseases of hematopoietic stem cells characterized by aberrant proliferation of mature myeloid lineages. The constitutive activation of the JAK2/STAT signaling pathway is now well established to play a central role in MPN pathogenesis; however, accumulating evidence now indicates that the IGF1R-mediated signaling pathway contributes to the maintenance of the malignant phenotype. Studies using inhibitors of IGF1-mediated signaling have reported cytotoxic effects in cellular and murine models of MPN, but no consensus has been reached regarding the potency and efficacy of inhibitors of the IGF1R-related pathway in this context. In the present study, we compared the potency and efficacy of three inhibitors of IGF1R-related pathways in a JAK2 V617F -driven cellular model. These inhibitors (NT157, OSI-906, and NVP-AEW54) present antineoplastic activity with similar efficacy in Ba/F3 JAK2 V617F cells, with NT157 showing the greatest potency. Both the induction of apoptosis and reduction in cell proliferation were associated with the observed reduction in cell viability. Downregulation of JAK2/STAT signaling was an advantageous off-target effect of all three inhibitors. These preclinical studies reinforce the potential of the IGF1R-related pathway as a therapeutic target in MPN. Highlights: Myeloproliferative neoplasms (MPN) are characterized by aberrant proliferation of mature myeloid lineages. IGF1R-mediated signaling pathway contributes MPN phenotype. The potency and efficacy of three inhibitors of IGF1R-related pathways were investigated. NT157 showed the greatest potency in MPN cellular models. Downregulation of JAK2/STAT signaling was an advantageous off-target effect of all three inhibitors.